(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
The late mixed dentition period (ages 9–12) is a critical stage in pediatric dentistry. Newly erupted permanent teeth have immature enamel, making them more susceptible to caries. Poor oral hygiene and dietary habits further increase the risk. Therefore, minimally invasive approaches are highly important.